The Moderating Role of Employees’ Humor Styles on the Relationship Between Job Stress and Emotional Exhaustion - Oktuğ, Bige Zeynep (Canadian Center of Science and Education, 2017)
In today’s work conditions, job stress and emotional exhaustion are serious threats for the health of employees. Previous research suggests a relationship between job stress and emotional exhaustion. The way individuals use humor has been associated with different coping strategies. The aim of this study is to investigate the moderating role of employees’ humor styles on the relationship between job stress and emotional exhaustion. 116 participants completed self-reported measures assessing their job stress, emotional exhaustion and humor styles. For data analyses a series of hierarchical moderated regression analyses were conducted. The findings show that self-enhancing and self-defeating humor styles have moderating effects on the relationship between job stress and emotional exhaustion. As the level of self-enhancing humor increases, the effect of job stress on emotional exhaustion is attenuated, on the other hand, as the level of self-defeating humor increases, the effect of job stress on emotional exhaustion is intensified. Findings regarding the effects of employees’ humor styles are discussed.
Keywords: humor styles; job stress; emotional exhaustion